2019
DOI: 10.17826/cumj.466375
|View full text |Cite
|
Sign up to set email alerts
|

İntihar amaçlı olmayan kendine zarar verme davranışı ve intihar ilişkisi; tanı, borderline kişilik bozukluğu ve mizaç ve karakter özelliklerinin rolü

Abstract: The aim of this study is to determine clinical diagnosis which will lead to prevention, treatment and keeping from reoccurrence of suicide among young adults with self injury behavior, and to determine borderline personality characteristics and temperament and character features. Materials and Methods: 18-20 year old 93 patients followed in Adolescent and Young Adult Psychiatry second step clinic, have been given deliberate self harm inventory, self harm behavior questoinnarie. and divided into two groups as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition, as seen in this systematic review, no studies were found in the Turkish sample to reduce self-harm behaviour and suicide attempts noticed in individuals diagnosed with borderline personality disorder. When the literature is examined, although there are descriptive studies examining the factors that predict self-harm behaviour and suicide attempts in individuals diagnosed with borderline personality disorder (Küçük andÇetinkaya 2019, Tunç ve Şahin 2019), the absence of any intervention studies shows that there is a critical gap in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as seen in this systematic review, no studies were found in the Turkish sample to reduce self-harm behaviour and suicide attempts noticed in individuals diagnosed with borderline personality disorder. When the literature is examined, although there are descriptive studies examining the factors that predict self-harm behaviour and suicide attempts in individuals diagnosed with borderline personality disorder (Küçük andÇetinkaya 2019, Tunç ve Şahin 2019), the absence of any intervention studies shows that there is a critical gap in this field.…”
Section: Discussionmentioning
confidence: 99%